Environmental health recommendations for Multidrug-Resistant Tuberculosis in low- and middle-income countries: a systematic review - Nel, Amy (Department of Public Health and Family Medicine, 2023)
Despite efforts towards the management and prevention of Tuberculosis (TB) having shown some success, Multidrug-Resistant Tuberculosis (MDR-TB) may potentially compromise these endeavours. MDR-TB has the potential to become the most dominant form of TB in low- and middle-income countries (LMICs). The impact of environmental health factors on the optimization of health of MDR-TB infected individuals, as well as on the prevention of transmission to household contacts, is not well documented. Current Sustainable Development Goals (SDGs) aim to achieve inclusivity, sustainability and resilience, not only through economic and social changes, but also through environmental targets in order to achieve optimal health and well-being for all. However, without appropriate acknowledgment of the environment's influence on outcomes during TB treatment, these targets are potentially unattainable. Establishing the recommendations of environmental health risk factors for individuals living at home with MDR-TB will have important policy implications as well as assist in decision making for those affected with MDR-TB in LMICs, such as South Africa. This systematic review, therefore, sought to identify the environmental health factors in LMICs that affect treatment outcomes for individuals living at home with MDR-TB, to optimize their health during completion of their treatment regimen and prevent transmission to household contacts. Part A outlines the current literature available for such a topic as well as methodology used within the systematic search and analysis of included articles. Prominent environmental health exposure variables of interest that have previously been identified as having a significant role in TB transmission or influencing the well-being of infected individuals, were identified within the literature. These included air pollution, nutrition, migration, urbanization, smoking, alcohol, other substance use and housing. Outcomes of interest included optimization of health and prevention of MDR-TB transmission to household contacts. The article (part B) represents the results from the systematic search as well as the application to current policy recommendations. After screening and reviewing the full text of potential articles for inclusion (N = 87), only thirteen articles were eligible for inclusion into the final sample. All included studies were primary observational studies, examining the relationship between MDRTB and the pre-defined exposures and outcomes in populations ≥13 years of age. Environmental risk factors for household transmission of MDR-TB potentially included malnutrition but showed no significant relationship with overcrowding. There was disagreement as to whether smoking was as a significant predictor of mortality but findings did indicate that smoking did have a negative impact on sputum culture conversion among patients receiving treatment. Other substance use was found to have a significant role in the default of treatment. The use of alcohol was associated with poor treatment outcomes, default of treatment and lack of sputum culture conversion. In terms of household conditions, an association was found between substandard housing conditions and treatment default. Formal housing was associated with a decline in treatment default but a residential address change was associated with defaulting treatment. The results of the review presented contradictory results regarding the risk of mortality and underweight/overweight BMI estimates. The review potentially highlighted vulnerable population groups including gender groups, children and HIV positive individuals. Therefore, this systematic review highlighted the potential relationship between environmental risk factors and optimising the health of individuals on treatment for MDR-TB, as well as the role that promoting environmental health may play in preventing the transmission to household contacts. In conclusion, environmental risk factors should be incorporated into local health system strategies and global policy. This includes WHO targets in TB prevention efforts, as well as in action areas for the attainment of relevant SDGs (e.g. SDG 3 and SDG 5), to address the burden of MDR-TB and decrease MDR-TB transmission in LMICs, effectively and sustainably.